Thermal power plant pre-operational activities - Sarkar, Dipak K. (Elsevier, 2017)
Thermal Power Plants: Pre-Operational Activities covers practical information that can be used as a handy reference by utility operators and professionals working in new and existing plants, including those that are undergoing refurbishments and those that have been shut for long periods of time. It is fully comprehensive, including chapters on flushing boiler systems, various methods of testing steam generators, and the drying out of generators. This book will be invaluable for anyone working on the startup, commissioning, and operation of thermal power plants. It is also a great companion book to Sarkar’s Thermal Power Plant: Design and Operation. Sarkar has worked with thermal power plants for over 40 years, bringing his experience in design and operations to help new and experienced practicing engineers perform effective pre-operational activities.--Provided by publisher.